Three new species of moth flies (Diptera, Psychodidae, Psychodinae) from the Afrotropical Region - Ježek, Jan; Oboňa, Jozef (Zootaxa, 2019)
Type material of moth flies of Neoarisemus leponti sp. nov. was collected in Madagascar, Toamasina province, environments of Analamazaotra and Amboditafonana. Hemimormia nyangerensis sp. nov. and Iranotelmatoscopus kenyensis sp. nov. were captured in Equatorial Africa near Victoria Lake during a fieldwork in Uganda (Gaba) and Kenya (Kusa, Nyangera). The mentioned three species are described, differential diagnoses included, and diagnostic characters illustrated.